2021
DOI: 10.51486/jbo.v3i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Halal Product Guarantee for Micro Enterprises

Abstract: The implementation of Law Number 33 of 2014 concerning Halal Product Guarantee regulates the obligation of halal certification for business products. The obligation of dependent certification for micro business actors in harmonizing the program, it can be a challenge in itself considering the cost of certification is not cheap. The purpose of this study is to determine the implementation of halal product guarantees after the implementation of the Job Creation Law which changes some of the provisions of the Hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…even increasing the quantity of exports of Malaysian and Thai micro-enterprise products. Then the research results from Ariansyah, Asrul, & Eymal, in 2021 showed the same results, that the role of product development, product certification services, and digital marketing was able to increase 56% of sales levels and 48% of business actors were able to increase their market share through increasing capacity export (Abduh. 2021).…”
Section: Introductionmentioning
confidence: 89%
“…even increasing the quantity of exports of Malaysian and Thai micro-enterprise products. Then the research results from Ariansyah, Asrul, & Eymal, in 2021 showed the same results, that the role of product development, product certification services, and digital marketing was able to increase 56% of sales levels and 48% of business actors were able to increase their market share through increasing capacity export (Abduh. 2021).…”
Section: Introductionmentioning
confidence: 89%
“…Due to the many problems that have arisen, in 2014, the Government together with the DPR, drafted halal certification has undergone changes. The authority of LPPOM-MUI was initially turned into the authority of the Halal Product Guarantee Agency (BPJPH) under the authority of the Ministry of Religion (Abduh, 2021).…”
Section: Halal Certification In Law Number 33 Of 2014 Concerning Hala...mentioning
confidence: 99%
“…have not yet provided legal certainty and protection for the Islamic community (Abduh, 2021) Certification is the essence of implementing halal product guarantees for all products circulating and traded in the territory of Indonesia in accordance with the JPH Law (Putri, 2021) . After the JPH Law was promulgated, halal certification for products must run effectively within 5 years.…”
Section: Introductionmentioning
confidence: 99%